Pengaruh Transformational Leadership, Quality of Work Life, dan Organizational Commitment Terhadap Organizational Citizenship Behavior - Mala Septiani; Tantri Yanuar Rahmat Syah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
In the current development of the manufacturing industry, competition among companies has become increasingly intense, requiring organizations to encourage employee behaviors that go beyond formal job requirements, such as organizational citizenship behavior. This study aims to fill the knowledge gap regarding the influence of transformational leadership and quality of work life on organizational citizenship behavior with organizational commitment among employees of manufacturing companies in Tangerang. Data were collected through an online questionnaire in December 2025. The study employed LISREL analysis with a sample of 155 respondents selected using purposive sampling. The results indicate that quality of work life has a positive effect on organizational commitment. Transformational leadership positively affects both quality of work life and organizational citizenship behavior. Organizational commitment also positively influences organizational citizenship behavior. However, transformational leadership does not positively affect organizational commitment, and quality of work life does not positively affect organizational citizenship behavior. This study provides theoretical and practical contributions to human resource management, particularly regarding the role of transformational leadership, quality of work life, and organizational commitment in enhancing organizational citizenship behavior. Future research is expected to further examine extra-role behavior and its implications for organizational outcomes.